KEWENANGAN KOMISI PEMILIHAN UMUM DALAM MENUNJANG HAK MEMILIH BAGI PENYANDANG DISABILITAS TERHADAP PEMILIHAN BUPATI KABUPATEN ALOR - Koda, Taufik Sulaiman; Stefanus, Kotan Y; Ratu Udju, Hernimus (Petitum Law Journal, 2025)
This study examines the authority of the General Election Commission in supporting the voting rights of voters with disabilities during the 2018 Alor Regency Election. The General Election Commission effectively fulfilled its role through close coordination with ad hoc bodies and other stakeholders, focusing on improving accessibility at polling stations and conducting inclusive outreach programs. However, the Alor Regency General Election Commission faced various challenges in enhancing accessibility for voters with disabilities, including voter data changes, geographical conditions, and family attitudes toward individuals with disabilities. Additionally, internal challenges included a lack of understanding among Polling Station Working Group officers and limited resources. Despite these obstacles, the participation of voters with disabilities in the election was relatively satisfactory. These findings highlight the importance of continuous evaluation, capacity-building at the local level, and stronger support to ensure more inclusive elections in the future.